Bowel Management in Hirschsprung Disease-Pre-, Peri- and Postoperative Care for Primary Pull-Through - Judith Lindert; Felix Schulze; Stefanie Märzheuser (MDPI AG, 2024)
(1) Background: Bowel management contributes throughout the pathway of care for children with Hirschsprung. Preoperative bowel management prepares the child and family for the pull-through surgery. Perioperative bowel management supports early recovery and tailored bowel management in the follow-up supports the achievement of social continence. (2) Methods: We conducted a cross-sectional assessment of our institutional bowel management program to illustrate the pre-, peri- and postoperative bowel management strategies. (3) Results: A total of 31 children underwent primary pull-through, 23 without a stoma and 8 with a stoma, at a median age of 9 months. All children without a stoma were prepared for surgery by using rectal irrigations. Children with a stoma were prepared for surgery with a transfer of stoma effluent. Transanal irrigation supported early recovery. (4) Conclusions: Bowel management is a key pillar of the management of children with Hirschsprung disease. Incorporating bowel management in the pathway of care facilitates primary pull-through and supports perioperative recovery.